Pemanfaatan Waktu Luang (Leisure) Dalam Aktivitas Kehidupan Sehari-Hari Lansia Di Posyandu Kedung Gobyak Desa Sobokerto Kecamatan Ngemplak Boyolali - Ninik Nurhidayah (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Elders, Leisure Time. Utilization of leisure time is quite essential for the eldres’ life. Those activities may diminish and even eliminate the sense of incompetency and adjancent to it, the ability to perform this activities also promoting a comfort life condition. The research aimed to reveal the utilization of leisure time in the elders’ daily routine. The research was conducted in Kedung Gobyak Community Health Centre, Sobokerto, Ngemplak, Boyolali. A qualitative designed research which involving elder population in surounding area of Kedung Gobyak Community Health Centre, Sobokerto, Ngemplak, Boyolali. Five elders were chosen as part of purposive sampling technique continued with data collection process trough in-depth interview, subjects’ observation and documentation. Thematic data analysis was used as the data analysis method according to each founded themes. The research depicts the various activities of the elders’ during their leisure time such as sedentary activities (watching electronic media of entertainment, relaxation or sitting back without doing any activities), chatting or mingle with peers, light exercise, joining the community events and mild activities. Most of the respondents reported sitting back as their first preference. The utilization of leisure time is principal and valuable for elders to support their performance in the daily routine.